STRATEGIC COMPETENCE AS A DETERMINANT OF PROFESSIONAL COMPETENCE OF A FUTURE SPECIALIST - Levitina Lina (Вісник Університету імені Альфреда Нобеля. Серія Педагогіка і психология)
The article analyses the research and trends in various literary sources with the aim of identifying new theoretical concepts regarding the essence of strategic competence, with the help of which we can better understand the requirements for strategic competence of specialists to improve the professional training of future specialists. It has been established that the phenomenon of “strategic competence” is a complex and multidimensional phenomenon, so defining the essence of this phenomenon primarily involves clarifying the content of such a related concept as “competence”, on the basis of which it is possible to reveal the essence of the concept of “strategic competence” of a person. Competence in the study is considered as an integrative personal formation that combines the acquired knowledge, skills, abilities, experience and personal characteristics that determine the desire, ability and willingness to solve problems and tasks that arise in real life and professional situations. The analysis of the scientific literature has shown that there is a difficulty in defining strategic competence, as it can refer to both the ability to perform tasks and the way people should behave to fulfil their role. Based on the analysis of the structure of professional competence, we conclude that strategic competence is one of its important structural components. Strategic competence exists as part of the professional competence of a specialist of any profile, and should be used when there is a need to find solutions to real or foreseeable problems in professional activities. It is established that it is advisable to distinguish strategic competence as a separate component of professional competence. It is proved that strategic competence is closely related to higher education and the necessary requirements for graduates of higher education institutions. In the course of the analysis, it is found out that the content of the standards of higher education of Ukraine of the first (bachelor’s) level of higher education in various specialties takes into account the need to form strategic competence in future specialists. It is determined that a high level of formation of a specialist’s strategic competence ensures the choice of an effective model of professional behaviour that should meet the conditions of professional activity; planning and development by a specialist of measures to adapt to the conditions of professional activity, including changes in organizational culture; determination of the overall goal of professional activity; implementation of planned actions and operations; implementation of the planned strategy, etc. It is concluded that strategic competence is one of the components of professional competence, which provides solutions to real or foreseeable problems; this high level of formation of the strategic competence of a specialist ensures the choice of an effective model of professional behaviour that should meet the conditions of professional activity; planning and development by a specialist of measures to adapt to the conditions of professional activity, including changes in organizational culture; determination of the overall goal of professional activity; performance of planned actions and operations; implementation of the planned strategy, etc. The conducted research emphasizes the relevance of this issue in today’s conditions and provides prospects for further work on disclosing the essence and structure of the strategic competence of the head of a preschool education institution.